Discourse on Post-Divorce Distribution of Joint Assets in the Perspective of Islamic Law in Indonesia - Zainurohmah, Zainurohmah; Andini, Marcelia Puspa; Damayanti, Anisa Vira (Universitas Negeri Semarang, 2023)
The distribution of joint assets following divorce is a significant aspect of family law, particularly within the framework of Islamic law in Indonesia. This paper explores the discourse surrounding post-divorce asset distribution from an Islamic legal perspective, shedding light on the principles, practices, and challenges within the Indonesian context. Grounded in Islamic jurisprudence, the analysis delves into the principles governing asset distribution, including considerations of fairness, equity, and the well-being of family members. It examines the Quranic injunctions and Prophetic traditions that guide asset division, as well as the interpretations and applications of Islamic law by legal scholars and judicial authorities in Indonesia. Moreover, the paper scrutinizes the contemporary legal landscape and societal norms influencing post-divorce asset distribution in Indonesia. It addresses the evolving nature of family structures, economic dynamics, and gender roles, and their impact on asset division practices within Islamic law. Through a multidisciplinary approach encompassing Islamic studies, family law, and socio-legal analysis, this paper contributes to a deeper understanding of the complexities surrounding post-divorce asset distribution in the Indonesian context. By elucidating the intersection of Islamic legal principles, cultural norms, and modern legal frameworks, it aims to inform legal practitioners, policymakers, and scholars engaged in family law reform efforts and contribute to the promotion of justice and equity in family matters within Islamic societies.